Impact of multifocal soft contact lenses on the shape discrimination threshold under glare in myopic children - Huang, Cuiting; Li, Xiuting; Liu, Jufen; Wu, Jingjing; Wang, Yuqing; Lin, Lingli; Zhang, Jinfeng; Chen, Yanrong; Zhang, Zhaode; Li, Li (Frontiers in Medicine, 2025)
BackgroundMultifocal soft contact lenses (MFSCLs) are widely used to control myopia progression in children. However, their optical design may affect visual quality, especially under glare conditions, potentially influencing their daily visual performance.PurposeTo evaluate the impact of MFSCLs on shape discrimination threshold (SDT) under glare in myopic children by comparing changes in SDT under glare and non-glare conditions, with both MFSCLs and single vision spectacles.MethodsThirty-seven myopic children (37 eyes) were enrolled and fitted with both MFSCLs and single vision spectacles for binocular myopia correction. Assessments included uncorrected and corrected visual acuity, corneal curvature, pupil diameter (PD) in a dark environment, and SDT with glare (SDTon) and without glare (SDToff). Measurements of the right eye were analyzed. SDTs were compared between lens types and lighting conditions, and correlations with ocular parameters were evaluated.ResultsAll participants achieved optimal MFSCL fit. No significant difference in SDTon or SDToff was observed between MFSCLs and spectacles (P > 0.05). However, SDTs were significantly elevated under glare compared to non-glare conditions (P < 0.001). In the MFSCL group, SDTon was significantly correlated with PD in the dark (r = 0.336, p = 0.042), as was the glare-induced SDT change (SDTdiff; r = 0.354, p = 0.032). In the spectacle group, SDTdiff was significantly associated with spherical equivalent refractive error (r = 0.435, p = 0.007). No serious adverse events occurred, and mild corneal staining resolved with appropriate care.ConclusionMFSCLs did not significantly worsen SDTs under glare in myopic children compared to spectacles, suggesting they do not exacerbate disability under glare. These findings support the continued clinical use of MFSCLs for myopia management without compromising visual performance under glaring conditions.